Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Answer:
x1 = -½
x2 = -2
x3 = 3
Step-by-step explanation:
replace f (x) with 0: 0=2x³-x²-13x-6
moves the expression to the first member:
-2x³+x²+13x+6=0
rewrite the x² and 13x as a sum:
-2x³-x²+2x+x+12x+6=0
now pick up -x² from the expression:
-x²(2x+1)+2x²+x+12x+6=0
now pick up the x:
-x²(2x+1)+x(2x+1)+12x+6=0
now pick up 6:
-x²(2x+1)+x(2x+1)+6(2x+1)=0
finally pick up 2x + 1 and rewrite the x as a difference:
-(2x+1)(x²+2x-3x-6)=0 (+2x-3x is the x rewritten as the difference)
pick up x and -3:
-(2x+1)•[x(x+2)-3(x+2)]=0
pick up x + 2 and change the sign:
(2x+1)(x+2)(x-3)=0
now having this, we can solve the equations in x:
2x+1=0 ---> x=-½
x+2=0 ---> x=-2
x-3=0 ---> x=3
here are the three solutions:
x1 = -½
x2 = -2
x3 = 3
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.